The Capital Structure of Islamic-Compliant Firms: Is there a Financing Hierarchy? - Muncef Guizani (Asian Academy of Management Journal of Accounting and Finance, 2020)
This article examines whether the basic premises according to the pecking order theory (POT) provide an explanation for the capital structure choice of firms operating under Islamic principles. Random effect regressions were performed to test the POT applying data from a sample of 93 Islamic-compliant firms listed on Saudi stock market over the period of 2006 to 2016. The results show that sale-based instruments (Murabahah, Ijara) track the financial deficit quite closely followed by equity financing and as a last alternative to finance deficit, Islamic-compliant firms’ issue Sukuk. In the crisis period, these firms seem more reliant on equity, then on sale- based instrument and on Sukuk as last option. The study findings also indicate that the cumulative financing deficit does not wipe out the effects of conventional variables, although it is empirically significant. This provides no support for the POT attempts by Saudi Islamic-compliant firms.